THE ROLE OF GESTURE IN THE NOVELS "SILK" AND "NOVECENTO" BY A. BARICCO - Rasulova M. M. (Research Focus International Scientific Journal, 2025)
Gestures in literary texts serve as an essential tool for communication, emotional expression, and symbolic representation. This study explores the role of gestures in Alessandro Baricco’s novels Silk and Novecento, analyzing how they contribute to character development, narrative structure, and thematic depth. Gestures function as non-verbal cues that enhance storytelling, creating an additional layer of meaning beyond dialogue. Through the analysis of key scenes, the research demonstrates how gestures shape reader perception, influence character interactions, and reinforce the psychological and cultural context of the novels.